Optimizing Kindergarten Students' Reading with Picture Media and Storybooks: A Classroom Action Research at PGRI 2 Malang Kindergarten - Lutfiah Sari; Thao Thi Vu; Ambarin Mooznah Auleear Owodally; Siti Salwa Binti Talib; Mitra Samiei (Classroom Experiences, 2024)
This research aims to overcome boredom in classical learning at PGRI 2 Malang Kindergarten by testing the integration between learning in the classroom and outside the classroom. The approach used is qualitative approach with classroom action research method. Through two cycles of activities, teachers conduct planning, action implementation, observation, analysis, and reflection to improve children's independence in learning. The results showed that the integration of outdoor learning and indoor learning was able to increase children's independence, allowing them to learn through real, interesting and challenging experiences. It is recommended to educators and kindergarten education managers to implement this approach to provide a more meaningful learning experience for children.